Scott Biederman Oral History Interview - (:unkn) unknown (My University, 2012)
Scott Biederman managed the Eau Claire Bear semi-professional baseball team for many years and won several state WBA state titles. In this interview, Mr. Biederman discusses baseball in Eau Claire, Wisconsin, from Little League to upper lever baseball, as well as his time with the Bears organization.